How do different lighting conditions affect the vision and quality of life of people with glaucoma? A systematic review - Enoch, Jamie (Eye (Lond), 2019)
This article is a systematic review of evidence regarding the impact of different lighting conditions on the vision and quality of life (QoL) of people with primary open-angle glaucoma (POAG). A systematic literature search was carried out using CINAHL, MEDLINE, PsycARTICLES, PsycINFO, Embase, and Ovid Nursing Database for studies: published up to April 2019; including people diagnosed with POAG; and assessing visual function or QoL in response to changing lighting/luminance levels or glare. Two researchers independently screened studies for eligibility. Data were extracted from eligible studies regarding study design, participant characteristics, outcomes, and results. Quality of included studies was critically appraised. Of 8437 studies, 56 eligible studies were included. Studies investigated the effects of lighting on the following domains among people with POAG: QoL (18/56), psychophysical measures (16/56), functional vision (10/56), activities of daily living (10/56), and qualitative findings (2/56). POAG negatively affects low-luminance contrast sensitivity, glare symptoms, and dark adaptation time and extent. In vision-related QoL questionnaires, people with POAG report problems with lighting, glare, and dark adaptation more frequently than any other domain. These problems worsen with progressing visual field loss. Early-stage POAG patients experience significantly more difficulties in low-luminance or changing lighting conditions than age-matched controls (AMCs), challenging perceptions of early-stage POAG as asymptomatic. However, performance-based studies seldom show significant differences between POAG participants and AMCs on tasks simulating daily activities under non-optimal lighting conditions. Further research with larger samples is required to optimise ambient and task-oriented lighting that can support patients’ adaptation to POAG.